2021
DOI: 10.1016/j.ymgmr.2021.100728
|View full text |Cite
|
Sign up to set email alerts
|

CYP21A2 mutations in pediatric patients with congenital adrenal hyperplasia in Costa Rica

Abstract: Steroid 21-hydroxylase deficiency accounts for 95% of congenital adrenal hyperplasia (CAH) cases. Newborn screening has allowed for early detection of the disease, and currently, molecular analysis can identify the genotypes of these patients. Phenotype-genotype correlation has been well described in previous studies. In Costa Rica, there is no data about the genetic background of these patients, nor their phenotypic correlation. Design Observational, retrospective, descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Using the MLPA technique, the prevalence of large deletions and large gene conversions in the present study was found in 29/112 (25.9%) patients with the SW phenotype. The results were in agreement with the work of Ben Charfeddine et al, 2012, who reported gene deletion/conversion in 11/50 Tunisian patients (22%) ( Kharrat et al, 2004 ; Ben Charfeddine et al, 2012 ; Chi et al, 2019 ; Umaña-Calderón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Using the MLPA technique, the prevalence of large deletions and large gene conversions in the present study was found in 29/112 (25.9%) patients with the SW phenotype. The results were in agreement with the work of Ben Charfeddine et al, 2012, who reported gene deletion/conversion in 11/50 Tunisian patients (22%) ( Kharrat et al, 2004 ; Ben Charfeddine et al, 2012 ; Chi et al, 2019 ; Umaña-Calderón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…A recent evaluation of 3 years of screened newborns, CH referrals, and CH diagnoses confirmed the validity of the CH screening algorithm [ 1194 ]. The first mutation study of CAH patients from NBS identified an overabundance of cases with c.292 + 5G > A suggesting a possible founder effect [ 1195 ]. NBS expansion to include Wilson’s disease is also of interest because of the highest incidence globally (~1:20,000) [ 1196 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a few patients with the I173N mutation and severe SW form have also been reported [ 20 , 21 , 22 ]. One of our female patients was homozygous for the c.293-13C>G mutation, which is mainly associated with the SW form [ 23 ]. Only a few cases of SV CAH with the c.293-13C>G mutation have been diagnosed, according to the literature [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of our female patients was homozygous for the c.293-13C>G mutation, which is mainly associated with the SW form [ 23 ]. Only a few cases of SV CAH with the c.293-13C>G mutation have been diagnosed, according to the literature [ 23 ]. In two other patients, large deletions were found, compounded with severe mutations, c.293-13C>G/deletion, and I173N/deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation